The state of functioning transport, freight forwarding and logistics companies and their responses to the pandemic crisis - Furtak Klaudia (Management)
The article attempts to present, on the basis of the existing survey research (questionnaires and interviews), subject literature, internet data as well as personal experiences and observations of the author (an employee of an international transport and logistics company), the general data regarding the influence of the COVID-19 pandemic on the functioning of transport, freight forwarding and logistics companies (referred to as TFL companies) and, additionally, the responses of these companies to the pandemic crisis. The choice of this subject was made on the general assumption that the influence of the coronavirus pandemic on the functioning of TFL companies has not been uniform. And although, unquestionably, its most perceptible, negative and destructive force predominates, the existence of a positive impact, as a factor that accelerates and revives company development, is not impossible.